Immediate Attention Enhancement and Restoration From Interactive and Immersive Technologies: A Scoping Review - Barton, Adam C.; Sheen, Jade; Byrne, Linda K. (Frontiers in Psychology, 2020)
Interactive and immersive technologies such as video games, exergames, and virtual reality are typically regarded as entertainment mediums. They also offer a multitude of health and well-being benefits. They have the capacity to incorporate established well-being techniques (e.g., mindfulness, exercise, and play) and expose users to beneficial environment settings with greater ease, improved access, and a broader appeal. The authors conducted a scoping review to explore whether these technologies could be used to benefit attention in healthy adults; that is, in a regulatory sense such as during periods of cognitive fatigue or attention-critical tasks. Research efforts have typically focused on long term practice methods for attention enhancement with these technologies. Instead, this review provides the first attempt to unify a broad range of investigations concerned with their immediate impact on attention through state-change mechanisms. This applies the concept of attention state training and a growing evidence base which suggests meditative practices, exercise bouts, and nature exposures can provide short term improvements in attentional performance following brief interactions. A systematic search of MEDLINE, Embase, and PsycINFO databases resulted in 11 peer-reviewed articles (13 experimental trials) each including at least one objective measure of attention directly following the use of an interactive or immersive technology. Most of the studies assessed interactive technology use (i.e., videogames and exergames), compared with three immersive interventions in the form of virtual reality. The comparisons between baseline and post-intervention showed mostly no effect on attention, although there were five cases of improved attention. There were no instances of negative effects on attention. The results are significant considering mounting concerns that technology use could be detrimental for cognitive functioning. The positive effects reported here indicate a need to specify the type of technology in question and bring attention to positive vs. negative technology interactions. Implications for the literature concerning attention state training are discussed considering promising effects of technology exposures geared towards flow state induction. Significant gaps in the literature are identified regarding the implementation of traditional attention state training practices.